The negative implications of Russia’s doping scandal on the country’s international image - Kobierecka, Anna; Kobierecki, Michał Marcin (Eastern Review, 2019)
In December 2014, Russia was accused of developing a state-organized doping system in the second decade of the twenty-first century. The scandal resulted in many Russian athletes being banned from competing in the Olympics in Rio in 2016 and the IOC’s suspension of the Russian National Olympic Committee prior to the 2018 Winter Olympics in PyeongChang. The research presented in this article aims to answer the research question of whether the doping scandal actually affected the international image of Russia. The research was conducted with the use of frame analysis of public discourse. The hypothesis to be tested states that the Russian doping scandal contributed to the intensification of a negative external image of this state.